Effect of Smoking on Rat Basilar Artery: Correlation with Inducible Nitric Oxide Synthase and Endothelin Converting Enzyme-1 - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2009)
AIM: Smoking is an extremely important risk factor for subarachnoid hemorrhage and seems to increase rupture risk of unruptured aneurysms by accelerating their growth rate. The aim of the study was to investigate the effect of smoking on the luminal diameter with wall thicknesses of rat basilar arteries and to detect alterations of inducible nitric oxide synthase and endothelin-converting enzyme -1 in the endothelial cells. MATERIAL and METHODS: Rats were divided into two groups. The level of middle pons slices were embedded in paraffin before they were stained with hematoxylin and eosin. Rabbit anti-human inducible nitric oxide synthase and endothelin converting enzyme-1 antibodies were used. RESULTS: Significant decrease of the vessel luminal diameter and increase of the vessel wall thickness were found in chronic smokers in our study. There was a linear and significant (p=0,023, r=0,704) correlation between thickness of the wall and endothelin converting enzyme-1 immune reaction. Correlation was not found with inducible nitric oxide synthase (p>0.05). CONCLUSION: This study on the comparison of vessel luminal diameter and vessel wall thickness with inducible nitric oxide synthase and endothelin converting enzyme-1 immune reactions revealed that the main effect of smoking on the vessel wall is associated with endothelin converting enzyme-1.
Keywords: Nitric Oxide Synthase-2; Endothelin Converting Enyzme-1; Smoking; Basilar artery; Subarachnoid haemorrage; CEREBRAL-BLOOD-FLOW; ANEURYSMAL SUBARACHNOID HEMORRHAGE; CEREBROSPINAL-FLUID; ACUTE VASOCONSTRICTION; CIGARETTE-SMOKING; L-ARGININE; VASOSPASM; RISK; METALLOPROTEASE; ACTIVATION